2006
DOI: 10.1038/sj.jp.7211574
|View full text |Cite
|
Sign up to set email alerts
|

Choroid plexus cysts do not affect fetal neurodevelopment

Abstract: Objective: To determine whether an isolated finding of a choroid plexus cyst (CPC) during routine ultrasound is associated with altered fetal growth or development.Study design: Prospective, case-control study comparing 35 CPC cases to 67 controls. Neurobehavioral development assessment included 50 min long serial recordings of heart rate, motor activity and their interrelation at 24, 28, 32 and 36 weeks gestation. Growth measurement was based on three ultrasound evaluations of femur length, biparietal diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…The observed decline in fetal heart rate and corresponding increase in variability over segments within the second half of gestation was reported in the original Monograph (Sontag & Richards, 1938) and many times since (Nijhuis et al, 1998; Pillai & James, 1990b; Ribbert, Fidler, & Visser, 1991; Van Leeuwen, Lange, Bettermann, Gronemeyer, & Hatzmann, 1999), including individual cohorts subsumed in this analysis (DiPietro, Costigan, et al, 2006; DiPietro, Caulfield, et al, 2004; DiPietro et al, 2010). Prior quantification of variability has been based on a number of time dependent and independent methods computed over various intervals.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The observed decline in fetal heart rate and corresponding increase in variability over segments within the second half of gestation was reported in the original Monograph (Sontag & Richards, 1938) and many times since (Nijhuis et al, 1998; Pillai & James, 1990b; Ribbert, Fidler, & Visser, 1991; Van Leeuwen, Lange, Bettermann, Gronemeyer, & Hatzmann, 1999), including individual cohorts subsumed in this analysis (DiPietro, Costigan, et al, 2006; DiPietro, Caulfield, et al, 2004; DiPietro et al, 2010). Prior quantification of variability has been based on a number of time dependent and independent methods computed over various intervals.…”
Section: Discussionsupporting
confidence: 62%
“…That analysis revealed that the lagged relationships between maternal heart rate, skin conductance, and spontaneous fetal motor activity were instigated by fetal movement such that maternal heart rate and skin conductance demonstrated brief, phasic increases within 2 to 3 s of onset of a fetal movement (DiPietro, Irizarry, et al, 2004). This finding was replicated on another, sociodemographically distinct sample (DiPietro, Caulfield, et al, 2006). We have also documented a maternal physiological response when fetal motor activity is induced by a percussive external sound, despite maternal auditory masking (DiPietro, Voegtline, et al, 2013).…”
Section: Chapter 12 General Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Detection of choroid plexus cysts (CPCs) occurs in an estimated 0.5–3.6% of routine mid‐gestation ultrasound exams (Chinn et al , 1991; Kupferminc et al , 1994; Demasio et al , 2002; DiPietro et al , 2006). While isolated CPCs are generally considered to be soft markers and a minor variation from normal anatomy without functional significance, parents are often informed of their detection due to the increased incidence in fetuses with aneuploidy, although this practice has been the subject of substantial debate (Filly et al , 2004).…”
Section: Introductionmentioning
confidence: 99%
“…femur length, biparietal diameter, abdominal circumference, and head circumference) or aspects of fetal neurobehavioral functioning (i.e. fetal heart rate patterning, motor activity, and their inter‐relation) measured from 24 to 36 weeks of gestation (DiPietro et al , 2006). However, only two studies have extended investigation into the post‐neonatal time period; both are limited by sample size and methodological considerations.…”
Section: Introductionmentioning
confidence: 99%